Alternative water supply systems - Memon, Fayyaz Ali; Ward, Sarah (IWA Publishing, 2015)
The book provides insights into a range of aspects associated with alternative water supply systems and an evidence base (through case studies) on potential water savings and trade-offs. The information organized in the book is aimed at facilitating wider uptake of context specific alternatives at a decentralized scale mainly in urban areas.